Apseudomorph Tanaidacea from the continental shelf of Angola and Namibia with descriptions of three new species - Bochert, Ralf (Zootaxa, 2012)
Four apseudomorph tanaidaceans are recorded from benthos of the shelf off Angola and off northern Namibia (SouthWest Africa). Of these, three are new to science, one each in the genera Hemikalliapseudes, Calozodion andApseudopsis. The genus Hemikalliapseudes now contains four species, all described from West Africa (Angola andMauretania). The new species Hemikalliapseudes sebastiani sp. nov. is separated from other species of this genus byfeatures of several appendages, and the shape of the cephalothorax, pereonites and telson. The genus Calozodion ismainly distributed in the Atlantic and also in the Indian Ocean. Calozodion dominiki sp. nov. is the tenth representativeof the genus and is readily distinguished from all others in that the cheliped propodus of the male has only smallprocesses proximo-ventrally. The new species was widely distributed in the investigation area. Apseudopsis cuanzanussp. nov. is a new member of this species-rich and widely-distributed genus. It differs from the other species of this genusby a combination of several morphological features, including the absence of a dorsodistal spine on the pereopod 1merus, the lack of anterolateral spines on the pereonites, the shape of rostrum and by the absence of plumose setae on pereopod six basis.